A Study of Problems on Using Innovation for Teaching in the Demonstration School of Ramkhamhaeng University (Secondary School) - Thongprong, Thanomkhwan; Singprasong, Kanjana; Theerawit, Kanitsorn; Youngsapanan, Patcharinan; Sunthornklam, Pithchaya (Arts of Management Journal, 2020)
The objectives of this research were 1) to study and to compare the opinions of lecturers towards the problems of using innovation for the teaching of the Demonstration School Ramkhamhaeng University 2) to assign the policies the lecturers’ teaching and learning management development. The rating scale questionnaire was used as the research instrument. The researchers found that the reliability was 0.821. The sample size in the research was 92 lecturers: 47 males and 45 females. Most lecturers are holding the degree higher than Bachelor which are 74 and the rest of them are holding Bachelor Degree which are 18 lecturers. The results of research were found that 1) 96.7 % of lecturers in the school did not stay on their former innovation for learning. Additionally, 79.4% of them regularly developed their innovation for teaching. However, regarding the ongoing training of innovation for teaching, 45.8% of them thought that it was not so important for applying the contents from the training in their real teaching and learning situation 2) the researchers found that there was no significant difference between the lecturers’ sex but there was significantly different in terms of applying and planning innovations for teaching in the classroom 3) the lecturers’ education, there was statistically significant at .05 in terms of continuous innovation for teaching development and attending to the innovation for teaching training regularly.